Local Duplication of TIR-NBS-LRR Gene Marks Clubroot Resistance in Brassica napus cv. Tosca - Kopec, Piotr M.; Mikolajczyk, Katarzyna; Jajor, Ewa; Perek, Agnieszka; Nowakowska, Joanna; Obermeier, Christian; Chawla, Harmeet Singh; Korbas, Marek; Bartkowiak-Broda, Iwona; Karlowski, Wojciech M. (Frontiers in Plant Science, 2021)
Clubroot, caused by Plasmodiophora brassicae infection, is a disease of growing importance in cruciferous crops, including oilseed rape (Brassica napus). The affected plants exhibit prominent galling of the roots that impairs their capacity for water and nutrient uptake, which leads to growth retardation, wilting, premature ripening or death. Due to the scarcity of effective means of protection against the pathogen, breeding of resistant varieties remains a crucial component of disease control measures. The key aspect of the breeding process is the identification of genetic factors associated with variable response to the pathogen exposure. Although numerous clubroot resistance loci have been described in Brassica crops, continuous updates on the sources of resistance are necessary. Many of the resistance genes are pathotype-specific, moreover, resistance breakdowns have been reported. In this study, we characterize the clubroot resistance locus in the winter oilseed rape cultivar ‘Tosca’. In a series of greenhouse experiments, we evaluate the disease severity of P. brassicae-challenged ‘Tosca’-derived population of doubled haploids, which we genotype with Brassica 60K array and a selection of SSR/SCAR markers. We then construct a genetic map and narrow down the resistance locus to the 0.4 cM fragment on the A03 chromosome, corresponding to the region previously described as Crr3. Using Oxford Nanopore long-read genome resequencing and RNA-seq we review the composition of the locus and describe a duplication of TIR-NBS-LRR (TNL) gene. Further, we explore the transcriptomic differences of the local genes between the clubroot resistant and susceptible, inoculated and control DH lines. We conclude that the duplicated TNL gene is a promising candidate for the resistance factor. This study provides valuable resources for clubroot resistance breeding programs and lays a foundation for further functional studies on clubroot resistance.